Potential Value of Ornamental Horticulture MSME Assets: A Financial Evaluation Approach - Rahmat Saleh (Fast in Humanities, 2025)
This study aims to assess the potential value of the ornamental plant sector through a financial evaluation approach, with a focus on micro, small, and medium enterprises (MSMEs) in Indonesia. The main objective of this study is to evaluate the financial feasibility of ornamental plant projects using key indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Benefit-Cost Ratio (BCR). This study uses a financial analysis method that utilises projected cash flow and operational cost data over a five-year period. The results show that the ornamental plant project has a positive NPV of IDR 196,798,211, an IRR of 59.4%, and a Payback Period of 1 year, 9 months, and 14 days. This analysis confirms that the ornamental plant project is financially feasible for investment, with a fast return on investment and a cost-benefit ratio that indicates high efficiency. In conclusion, this study makes an important contribution to the development of the ornamental plant sector, particularly in the context of MSMEs, and provides useful practical guidance for investment decision-makers in this industry.